Food composition table of selected local tree species in Burkina Faso. Version 1 - Vinceti, Barbara; Fallas Conejo, Diego Alberto; Odongo, Nicanor Obiero; Termote, Céline (Bioversity International, 2022)
Food composition tables (FCT) inform on the nutritional composition of foods consumed and are an essential resource for understanding and analyzing dietary intake data related to both individuals and communities, and for developing healthy recipes and food products. They are a fundamental piece of knowledge to support interventions related to improving nutrition, health, and food security in all contexts. They can also be used to assist forest landscape restoration initiatives based on tree planting, as these represent an opportunity to enhance the availability, access, and use of food tree species. Particularly for neglected and underutilized tree species, nutritional data are rarely available. The FCT included in this booklet selectively incorporate existing information and help to clearly spot the gaps, which should be addressed by further documentation efforts. The compilation of food composition data presented here focuses on 97 foods from 37 tree species from Burkina Faso, largely indigenous, with few exceptions, and undomesticated. Data were gathered through an extensive review of the literature and were compiled following international standards, i.e. guidelines and tools of the International Network of Food Data Systems (INFOODS).